Besov Characteristic of a Distribution - Vedel, Béatrice (Revista Matemática Complutense, 2007)
The Besov characteristic of a distribution f is the function sf defined for 0 _ t < 1 by sf (t) = sup{ s 2 R; f 2 Bs